Conservative and transformative changes in algebra in Swedish lower secondary textbooks 1995–2015 - Palm Kaplan, Kristina; Prytz, Johan (NOMAD Nordic Studies in Mathematics Education, 2020)
The present study examines textbook algebra tasks in an attempt to understand how textbooks change in a reform of lower secondary school algebra. Changes in 1557 textbook tasks for year 8 are described in terms of algebraic activities and school algebra discourses. The tasks were taken from textbooks published before and after a new syllabus was introduced in Sweden in 2011. The results show that the new syllabus’ focus on mathematical competences was not stressed in the textbooks and that the greatest change was an increase in word problems connected to everyday situations. It is suggested that, in this reform, textbooks have been conservative and transformative in relation to the syllabus.